Development of a New Electrochemical Sensor Based on Mag-MIP Selective Toward Amoxicillin in Different Samples - Lopez, Rosario (2021)
This project was supported by FONDECYT-BM (grant #0232019-FONDECYT-BM-IN.INV), FAPESP (grants #2019/006777 and #2014/50945-4), CNPq (grants #301728/2019-4, #408050/2018-7 and #465571/2014-0), and CAPES (PROJ. AUX/PE/PROEX N. 0674/2018). RL and GP received financial support from the OGI, Research Management Bureau (Project FC-F-6-2018).